Erosion, corrosion & chemical attack. Issue 2 (February 2017) - Unknown
Abstract : As we've reported before, paper mill pumps are put under immense strain due to the transfer of viscous material during the pulping process. This article looks at how one company was able to extend the life of pumps at an Italian paper mill with protective coatings.